Trends of calcium silicate biomaterials in medical research and applications: A bibliometric analysis from 1990 to 2020 - Yin, Hua; Yang, Xiaoli; Peng, Lisi; Xia, Chuanchao; Zhang, Deyu; Cui, Fang; Huang, Haojie; Li, Zhaoshen (Frontiers in Pharmacology, 2022)
Calcium silicate biomaterials (CSB) have witnessed rapid development in the past 30 years. This study aimed to accomplish a comprehensive bibliometric analysis of the published research literature on CSB for biomedical applications and explore the research hotspot and current status. Articles related to CSB published in the last three decades (1990-2020) were retrieved from Web of Science Core Collection. The R bibliometrix package and VOSviewer were used to construct publication outputs and collaborative networking among authors, their institutes, countries, journals’ matrices and keywords plus. A total of 872 publications fulfilling the search criteria were included. CSB is mainly reported for bone tissues and dental applications. Among researchers, Chang J from Chinese Academy of Sciences and Gandolfi MG from the University of Bologna are the most productive author in these two fields, respectively. China was the leading contributor to the research on CSB in the medical field. A total of 130 keywords appeared more ten or more times were identified. The term “mineral trioxide aggregate” ranked first with 268 occurrences. The co-occurrence analysis identified three major clusters: CSB in dentistry, bone tissue and vitro bioactivity.Calcium silicate biomaterials have a promising scope for various biomedical applications ranging from regeneration of hard tissues (bone and teeth) to skin, tumor, cardiac muscle and other soft tissues. This study may help researchers further understand the frontiers of the field.